تكنولوجيا المعلومات ودورها في التطبيب عن بعد: Information technology and its role in telemedicine - Akoush, Najwa Waheed; Bin Hashim, Hasnizam; Fadhlina Binti Alias; Binti Mohd, Zizi Azlinda (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث في المشهد المتطور باستمرار للرعاية الصحية، يظهر الاندماج المعقد لتكنولوجيا المعلومات والتطبيب عن بعد كقوة قوية تعيد تشكيل الممارسات الطبية. يسعى هذا البحث إلى استكشاف الدور متعدد الأوجه لتكنولوجيا المعلومات بشكل شامل في زيادة وتحويل التطبيب عن بعد. تتعمق الدراسة في التأثير العميق لأدوات ومنصات تكنولوجيا المعلومات على إمكانية الوصول إلى الرعاية الصحية، وديناميكيات الاتصال بين مقدمي الخدمات والمرضى، والكفاءة الشاملة لأنظمة تقديم الرعاية الصحية. مع التركيز الشديد على تسهيل الاستشارات عن بعد ومراقبة المريض في الوقت الفعلي، يدرس البحث بدقة التحديات والفرص المضمنة في هذا التكامل التكنولوجي. تحتل قضايا أمن البيانات وقابلية التشغيل البيني والتوزيع العادل للموارد مركز الصدارة، مما يتطلب دراسة متأنية لضمان النشر الأخلاقي والفعال لتكنولوجيا المعلومات في التطبيب عن بعد. باستخدام منهجية بحث قوية، تحتضن هذه الدراسة توليفة من مراجعات الأدبيات ودراسات الحالة والمقابلات النوعية مع المتخصصين في الرعاية الصحية وخبراء تكنولوجيا المعلومات. من خلال هذا النهج الشامل، يهدف البحث إلى تقديم رؤى دقيقة لا توضح فقط الوضع الحالي لتكنولوجيا المعلومات في التطبيب عن بعد ولكن أيضا إبلاغ قرارات السياسة وتوجيه ممارسي الرعاية الصحية في الاستفادة من التكنولوجيا لتحسين رعاية المرضى. من خلال توقع التحديات ومعالجتها، يساهم البحث في الخطاب المستمر حول تقاطع التكنولوجيا والرعاية الصحية، وتقديم حلول عملية لتعزيز كفاءة وفعالية ممارسات التطبيب عن بعد. تشمل النتائج المتوقعة فهما شاملا للمشهد الحالي، وتحديد التحديات الرئيسية، ورؤى ثاقبة للحلول المحتملة، وبالتالي تعزيز نهج أكثر استنارة واستجابة لدمج تكنولوجيا المعلومات في تشكيل المسار المستقبلي لتقديم الرعاية الصحية. ABSTRACT In the ever-evolving landscape of healthcare, the intricate fusion of Information Technology (IT) and Telemedicine emerges as a powerful force reshaping medical practices. This research seeks to comprehensively explore the multifaceted role of IT in augmenting and transforming Telemedicine. The study delves into the profound impact of IT tools and platforms on healthcare accessibility, communication dynamics between providers and patients, and the overarching efficiency of healthcare delivery systems. With a keen focus on the facilitation of remote consultations and real-time patient monitoring, the research meticulously examines the challenges and opportunities embedded in this technological integration. Issues of data security, interoperability, and the equitable distribution of resources take center stage, demanding careful consideration to ensure the ethical and effective deployment of IT in Telemedicine. Employing a robust research methodology, this study embraces a synthesis of literature reviews, case studies, and qualitative interviews with healthcare professionals and IT experts. Through this comprehensive approach, the research aims to provide nuanced insights that not only elucidate the current state of IT in Telemedicine but also inform policy decisions and guide healthcare practitioners in leveraging technology for improved patient care. By anticipating and addressing challenges, the research contributes to the ongoing discourse on the intersection of technology and healthcare, offering practical solutions to enhance the efficiency and efficacy of Telemedicine practices. The expected outcomes encompass a thorough understanding of the present landscape, the identification of key challenges, and insights into potential solutions, thereby fostering a more informed and responsive approach to the integration of IT in shaping the future trajectory of healthcare delivery.